>30 dB Suppression of Intrinsic Backscattering in Whispering-Gallery-Mode Microresonators - Svela, Andreas O.; Silver, Jonathan M.; Del Bino, Leonardo; Zhang, Shuangyou; Woodley, Michael T.M.; Vanner, Michael R.; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
We demonstrate a technique for suppressing backscattered light in a whispering-gallery-mode resonator by positioning a sub-wavelength-size scatterer within its evanescent field, achieving at least 34 dB suppression compared to the intrinsic backscattering.
CRIS-Team Scopus Importer:2021-12-24

4-Field Symmetry Breakings in Microresonator-Based Photonic Molecules - Ghosh, Alekhya; Hill, Lewis; Oppo, Gian Luca; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Spontaneous symmetry breaking (SSB) is said to have occurred when two or more properties of a system suddenly change from having equality between them (symmetric) to having an inequality (asymmetric) following an infinitely small change to some system parameter. Recently there has been rapid growth of research on SSB in Kerr resonators, for examples, between two counterpropagating light fields [1], and two orthogonally polarized modes [2]. In this work [3], we describe novel mechanisms for SSB, which cause four field symmetry breakings [4] in two different photonic molecule structures (two coupled ring resonators) with different field coupling mechanisms.
CRIS-Team Scopus Importer:2024-12-16

A Kerr Oscillator based on Counterpropagating Light in a Microresonator - Woodley, Michael T.M.; Hill, Lewis; Del Bino, Leonardo; Oppo, Gian Luca; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
We present experimental and numerical evidence of self-switching behaviours between counterpropagating optical modes in a Kerr microresonator [1]. Switching indicates the restoration on average of symmetry in a previously symmetry-broken state [2] , [3]. The time-evolution of the electric field amplitudes, E ± , of the two counter-propagating modes is accurately described by the following coupled system of ordinary differential equations: equation-dE- ± dt = E-in - [ 1 + i( θ - A| E- ± |ˇ2 - B| E- |ˇ2 ) ]E- ± equation-
CRIS-Team Scopus Importer:2021-10-29

Bright Microresonator Solitons in the Normal Dispersion Regime - Zhang, Shuangyou; Bi, Toby; Del'Haye, Pascal (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We report the first experimental observation of bright single soliton states in the normal dispersion regime of a microresonator. The soliton generation can be explained by higher order dispersion.
CRIS-Team Scopus Importer:2024-10-04

Characterization of Light Scattering in Microresonator via Symmetry Breaking of Counterpropagating Light - Pal, Arghadeep; Ghosh, Alekhya; Yan, Haochen; Bi, Toby; El Mazbouh, Ibrahim; Zhang, Shuangyou; Hill, Lewis; Del'Haye, Pascal (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
Many applications of microresonators in sensing, telecommunications, designing optical filters [1], generating low-threshold frequency combs [2] and demonstrating spontaneous symmetry breaking (SSB) of light fields [3-5] are affected by the losses in microresonators. These losses increase the threshold power for observing nonlinear interactions. While previous works [6] aimed at measuring absorptive losses in microresonators, the other major contribution to the total losses result from scattering induced by sidewall roughness, and the presence of scatterers in the optical path. We study the spatial distribution of scatterers in a microresonator, and determine the directionality and magnitude of the scattered light, thereby obtaining a unique fingerprint of the system.
CRIS-Team Scopus Importer:2025-09-26

Comparison of Dark Temporal Cavity Solitons in Fabry-Pérot and Ring Resonators with Normal Dispersion - Campbell, Graeme N.; Hill, Lewis; Del'Haye, Pascal; Oppo, Gian Luca (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Bright and dark temporal cavity solitons are of interest for the generation of highly stable optical frequency combs. Here we characterise dark temporal cavity solitons generated in a Fabry-Pérot (FP) resonator with normal dispersion and make comparison to their counterparts generated in ring resonator systems. We consider a high finesse FP resonator filled with a Kerr material and driven by linearly polarized light, see Fig. 1a. This system has been described in the anomalous dispersion regime in [1] where a so called FP Lugiato-Lefever equation has been derived and investigated. For normal dispersion this equation takes the form (equation presented) which describes the intracavity field ψ with input field S and detuning to the nearest cavity resonance θFP. Here t,ζ are the slow time and fast time variables describing the evolution over many round trips and single round trip tR respectively. The term with angled brackets corresponds to the average power of the field over a round trip of the resonator and arises from the inherent counterpropagation of intracavity fields in a FP configuration. Integral terms of this kind are also present in bidirectionally pumped ring resonators where, however, there are two coupled equations, one for each counterpropagating field [2,3].
CRIS-Team Scopus Importer:2024-12-16

Controlled Power Distribution in Microresonator Chains via Concurrent Symmetry Breakings - Ghosh, Alekhya; Pal, Arghadeep; Hill, Lewis; Del'Haye, Pascal (CLEO: Fundamental Science, CLEO:FS 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
We show the control of optical power patterns in coupled resonators optical waveguides (CROW) via the Kerr effect. This has applications in photonic integrated circuits, especially for light steering, sensors, and optical computing.
CRIS-Team Scopus Importer:2024-10-25

Controlling Frequency Comb Line Spacing Via Symmetry Broken Faticons - Hill, Lewis; Lucas, Erwan; Ghosh, Alekhya; Mazo Vásquez, Juan Diego; Gohsrich, Julius T.; Pal, Arghadeep; Yan, Haochen; Del'Haye, Pascal; Oppo, Gian Luca; Coen, Stéphane; Kunst, Flore K.; Fatome, Julien (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
Recently, a novel temporal structure known as the faticon has been identified within ring resonators composed of Kerr materials [1]. An example of a faticon is shown in Fig. 1(a), where its unique structure is seen to depend on two interlocked field components, |E±|2. These components co-propagate within the ring resonator but exhibit left- and right-circular polarizations, respectively. Faticons were initially predicted through a coupled set of (normalized) Lugiato-Lefever equations and have since been experimentally observed [1]. A key mechanism enabling the existence of a faticon is the spontaneous symmetry breaking (SSB) of light [2-5], wherein the symmetry between the two field components' intensities |E+|2 and |E-|2 spontaneously breaks (|E+|2 ≠ |E-|2) due to an infinitesimal change in a system parameter, such as the cavity detuning θ.
CRIS-Team Scopus Importer:2025-09-26

Counterpropagating light in ring resonators: Switching fronts, plateaus, and oscillations - Campbell, Graeme N.; Zhang, Shuangyou; Del Bino, Leonardo; Del'Haye, Pascal; Oppo, Gian-Luca (Physical Review A, 2022)
We characterize the formation of robust stationary states formed by light plateaus separated by two local switching fronts in only one of two counterpropagating fields in ring resonators with normal dispersion. Such states are due to global cross coupling and allow for frequency combs to switch from one field to the other by simply tuning the input laser frequency. Exact expressions for the distance between fronts and for plateau powers are provided in excellent agreement with simulations. These demonstrate an unusual high degree of control over pulse and plateau duration in one of the fields upon changes of one of the input laser frequencies. We identify a wide parameter region in which light plateaus are self-starting and are the only stable solution. For certain values of the detunings we find multistable states of plateaus with switching fronts, slowly oscillating homogeneous states and nonoscillating homogeneous states of the counterpropagating fields. Robustness and multistability of these unusual single-field front solutions are provided in parameter ranges that are experimentally achievable in a wide variety of ring resonators.
CRIS-Team WoS Importer:2022-11-18

Critical dynamics of an asymmetrically bidirectionally pumped optical microresonator - Silver, Jonathan M.; Grattan, Kenneth T.; Del'Haye, Pascal (Physical Review A, 2021)
An optical ring resonator with third-order, or Kerr, nonlinearity will exhibit symmetry breaking between the two counterpropagating circulating powers when pumped with sufficient power in both the clockwise and counterclockwise directions. This is due to the effects of self- and cross-phase modulation on the resonance frequencies in the two directions. The critical point of this symmetry breaking exhibits universal behaviors including divergent responsivity to external perturbations, critical slowing down, and scaling invariance. Here we derive a model for the critical dynamics of this system, first for a symmetrically pumped resonator and then for the general case of asymmetric pumping conditions and self- and cross-phase modulation coefficients. This theory not only provides a detailed understanding of the dynamical response of critical-point-enhanced optical gyroscopes and near-field sensors, but is also applicable to nonlinear critical points in a wide range of systems.
CRIS-Team Scopus Importer:2021-10-29

Dark-Bright Soliton Bound States in a Microresonator - Zhang, Shuangyou; Bi, Toby; Ghalanos, George N.; Moroney, Niall P.; Del Bino, Leonardo; Del'Haye, Pascal (Physical Review Letters, 2022)
Dissipative Kerr solitons in microresonators have facilitated the development of fully coherent, chipscale frequency combs. In addition, dark soliton pulses have been observed in microresonators in the normal dispersion regime. Here, we report bound states of mutually trapped dark-bright soliton pairs in a microresonator. The soliton pairs are generated seeding two modes with opposite dispersion but with similar group velocities. One laser operating in the anomalous dispersion regime generates a bright soliton microcomb, while the other laser in the normal dispersion regime creates a dark soliton via Kerr-induced cross-phase modulation with the bright soliton. Numerical simulations agree well with experimental results and reveal a novel mechanism to generate dark soliton pulses. The trapping of dark and bright solitons can lead to light states with the intriguing property of constant output power while spectrally resembling a frequency comb. These results can be of interest for telecommunication systems, frequency comb applications, and ultrafast optics.
CRIS-Team WoS Importer:2022-02-11

Dark-Bright Soliton Frequency Combs in a Microresonator - Zhang, Shuangyou; Bi, Toby; Ghalanos, George N.; Moroney, Niall P.; Del Bino, Leonardo; Del'Haye, Pascal (Optics InfoBase Conference Papers, 2022)
We demonstrate mutually trapped dark-bright-soliton pairs in microresonators. The solitons are generated by seeding modes in different dispersion regimes with similar group velocity. Dark-bright-soliton pairs enable frequency combs with nearly constant power in time domain.
CRIS-Team Scopus Importer:2022-09-09

Dark-Bright Soliton Pairs in a Microresonator - Zhang, Shuangyou; Bi, Toby; Ghalanos, George N.; Moroney, Niall P.; Bino, Leonardo Del; Del'Haye, Pascal (2022 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2022 - Proceedings, 2022)
Mutually trapped dark-bright soliton pairs are demonstrated in a microresonator by seeding modes in different dispersion regimes with similar group velocity. Dark-bright-soliton pairs enable frequency combs with nearly constant power in time domain.
CRIS-Team Scopus Importer:2024-12-16

Dark Temporal Cavity Soliton Pairs in Fabry-Pérot Resonators with Normal Dispersion and Orthogonal Polarizations - Campbell, Graeme N.; Hill, Lewis; Del'Haye, Pascal; Oppo, Gian Luca (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Temporal cavity solitons have attracted significant interest for optical frequency comb generation with a large number of applications including precision spectroscopy, LIDAR, and channel generation for telecom systems [1]. Here we introduce dark and dark-bright vectorial temporal cavity soliton pairs in a Fabry-Pérot (FP) resonator with normal dispersion and two orthogonal polarizations. A FP resonator with highly reflective mirrors, Fig. 1a, which contains a normally dispersive Kerr medium and driven by an input field with two orthogonal polarizations can be modeled [2] with the following system of two integro-partial differential equations (equation presented) where ψ± are the fields of left and right handed circular polarization with input fields S and detuning to the nearest cavity resonance θ. Here t,ζ are the slow time and fast time variables describing the evolution over many round trips and single round trip tR respectively. Integral terms correspond to angled brackets and take the form of global averages in the fast time over a round trip of the resonator. They arise due to the counterpropagation of the fields inherent in a FP configuration or in bidirectionaly pumped ring resonators [3].
CRIS-Team Scopus Importer:2024-12-16

Enhanced Frequency Combs via Self-Crystallizing Cavity Solitons - Campbell, Graeme N.; Hill, Lewis; Del'Haye, Pascal; Oppo, Gian Luca (CLEO: Fundamental Science, CLEO:FS 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
A “self-crystallization” phenomenon of dark vectorial temporal cavity solitons can occur in Fabry-Pérot resonators, with major applications in frequency comb generation. This phenomenon arises from the long-range interactions between symmetry-broken light fields with orthogonal polarizations.
CRIS-Team Scopus Importer:2024-10-25

Fifth-order Dispersion Soliton in a Microresonator - Zhang, Shuangyou; Bi, Toby; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
We investigate the dynamics of continuous-wave-laser-driven soliton generation in the zero-group-velocity-dispersion regime in a microresonator. We show that the observed solitons are enabled by fifth-order dispersion.
CRIS-Team Scopus Importer:2023-11-24

Four-field symmetry breakings in twin-resonator photonic isomers - Ghosh, Alekhya; Hill, Lewis; Oppo, Gian Luca; Del'Haye, Pascal (Physical Review Research, 2023)
Symmetry and symmetry breaking of light states play an important role in photonic integrated circuits and have recently attracted lots of research interest that is relevant to the manipulation of light polarization, telecommunications, all optical computing, and more. We consider four-field symmetry breaking within two different configurations of photonic dimer systems, both comprised of two identical Kerr ring resonators. In each configuration we observe multiple degrees and levels of spontaneous symmetry breaking between circulating photon numbers and further, a wide range of oscillatory dynamics, such as chaos and multiple variations of periodic switching. These dynamics are of interest for optical data processing, optical memories, telecommunication systems, and integrated photonic sensors.
CRIS-Team Scopus Importer:2024-12-16

Generalized theory of optical resonator and waveguide modes and their linear and Kerr nonlinear coupling - Silver, Jonathan M.; Del'Haye, Pascal (Physical Review A, 2022)
We derive a general theory of linear coupling and Kerr nonlinear coupling between modes of dielectric optical resonators from first principles. The treatment is not specific to a particular geometry or choice of mode basis, and can therefore be used as a foundation for describing any phenomenon resulting from any combination of linear coupling, scattering, and Kerr nonlinearity, such as bending and surface roughness losses, geometric backscattering, self- and cross-phase modulation, four-wave mixing, third-harmonic generation, and Kerr frequency comb generation. The theory is then applied to a translationally symmetric waveguide in order to calculate the evanescent coupling strength to the modes of a microresonator placed nearby, as well as the Kerr self- and cross-phase modulation terms between the modes of the resonator. This is then used to derive a dimensionless equation describing the symmetry-breaking dynamics of two counterpropagating modes of a loop resonator and prove that cross-phase modulation is exactly twice as strong as self-phase modulation only in the case that the two counterpropagating modes are otherwise identical.
CRIS-Team Scopus Importer:2022-03-18

Geometry optimization for dark soliton combs in thin multimode silicon nitride microresonators - Zhang, Yaojing; Zhang, Shuangyou; Bi, Toby; Del'Haye, Pascal (Optics Express, 2023)
Silicon nitride (Si3N4) has been well established as an ultralow-loss material for integrated photonics, particularly for the generation of dissipative Kerr soliton frequency combs, enabling various applications for optical metrology, biological imaging, and coherent telecommunications. Typically, bright soliton generation in Si3N4 devices requires thick (>600 nm) films to fulfill the condition of anomalous dispersion at telecom wavelengths. However, thick films of ultralow-loss Si3N4 (>400 nm) often suffer from high internal stress, leading to cracks. As an alternative approach, thin Si3N4 films (<400 nm) provide the advantage of one-step deposition and are widely applied for commercial use. Here, we provide insights into engineering an integrated Si3N4 structure that achieves optimal effective nonlinearity and maintains a compact footprint. A comparative analysis of Si3N4 resonators with varying waveguide thicknesses is conducted and reveals that a 400-nm thin Si3N4 film emerges as a promising solution that strikes a balance among the aforementioned criteria. Based on a commercially available 400-nm Si3N4 film, we experimentally demonstrate the generation of low-noise coherent dark pulses with a repetition rate of 25 GHz in a multimode Si3N4 resonator. The compact spiral-shaped resonator has a footprint of 0.28 mm2 with a high-quality factor of 4 × 106. Our demonstrated dark combs with mode spacings of tens of GHz have applications in microwave photonics, optical spectroscopy, and telecommunication systems.
CRIS-Team Scopus Importer:2023-12-15

Hz-level Broadband Spectroscopy with a Dual-Modulated Tunable Diode Laser - Zhang, Shuangyou; Bi, Toby; Del'Haye, Pascal (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We demonstrate Hz-level broadband spectroscopy using a dual radio frequency modulated diode laser referenced to a fiber cavity. This approach offers great simplicity, robustness and low costs, making it well-suited for out-of-the-lab applications.
CRIS-Team Scopus Importer:2024-10-04

Imaging of standing-wave patterns from a bi-directionally pumped microresonator - Yan, Haochen; Ghosh, Alekhya; Pal, Arghadeep; Zhang, Hao; Bi, Toby; Ghalanos, George; Zhang, Shuangyou; Hill, Lewis; Zhang, Yaojing; Zhuang, Yongyong; Xavier, Jolly; Del'Haye, Pascal (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We perform real-time imaging of standing waves in bi-directionally pumped microresonators. This is achieved by collecting scattered light with a short-wave infrared camera. The measurements enable subwavelength distance measurements of scattering sources with nanometer-level accuracy.
CRIS-Team Scopus Importer:2024-10-04

Integrated Femtosecond Pulse Amplifier - Gaafar, Mahmoud A.; Ludwig, Markus; Wang, Kai; Wildi, Thibault; Voumard, Thibault; Sinobad, Milan; Lorenzen, Jan; Francis, Henry; Zhang, Shuangyou; Bi, Toby; Del'Haye, Pascal; Geiselmann, Michael; et al. (CLEO: Applications and Technology, CLEO: A and T 2024 in Proceedings CLEO 2024 - Part of Conference on Lasers and Electro-Optics, 2024)
We demonstrate for the first-time f emtosecond p ulse a mplification in a CMOS-compatible photonic chip. We report >50-fold amplification of 1 GHz-repetition-rate chirped femtosecond pulses to 800 W of on-chip peak power with 116 fs pulse duration.
CRIS-Team Scopus Importer:2024-10-04

Inverse Designed Silicon Nitride Photonic Linear Microresonators - Bi, Toby; Zhang, Shuangyou; Ghosh, Alekhya; Zhang, Yaojing; Ohletz, Olga; Harder, Irina; Yang, Kiyoul; Del'Haye, Pascal (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We fabricate and characterize silicon nitride microresonators formed between pairs of inverse-designed integrated photonic mirrors. These type of Fabry-Pérot cavities can be used for nonlinear optics and Kerr soliton generation in dispersion engineered resonators.
CRIS-Team Scopus Importer:2024-10-04

Inverse Design of Microresonators Using Machine Learning - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Shuangyou; Bi, Toby; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
The rapidly increasing number of ways to fabricate integrated microresonators have led to a demand for optimization of such structures based on the desired optical properties. Tweaking the geometry of photonic structures can alter their dispersion profiles, which can counter optical nonlinearities and influence the intracavity optical dynamics. The parameter Dint describes the integrated dispersion which can be written as, (Equation presented) Here, ωm is the angular resonance frequency of the mth mode with respect to the pump mode m0 at angular pump frequency ω0. D1 refers to the angular free spectral range around the pump mode. Conventional photonic inverse design works [1,2] start with a design from empirical knowledge and then iteratively optimize the structure, which is both time-consuming and also requires additional quality factor engineering. However, machine learning (ML) being a faster alternative has shown significant applications in the field of photonics [3,4]. In this work [5], ML is used to predict the structure of a micro-ring Si3N4 resonator based on the desired dispersion profile. The regressor model is trained using 75% of the dispersion dataset simulated using a finite element method. For generating the simulation dataset around the wavelength of 1 μm to 2 μm, the radii, widths and heights of the core are varied in ranges close to the resonators fabricated in our lab from sputtered Si3N4 film [6]. Two ML algorithms, Decision Tree (DT) and Random Forest (RF), are compared. RF yielded better prediction results.
CRIS-Team Scopus Importer:2024-12-16

Kerr Enhancement of Optomechanics in Microresonators - Ghalanos, George N.; Silver, Jonathan M.; Zhang, Shuangyou; Del Bino, Leonardo; Bi, Toby; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
When on-chip microresonators were first fabricated in 2005, it became apparent that these cavities exhibit op-tomechanical properties, evident by the parametric oscillation instability that was observed [1], [2]. This behaviour, resulting from radiation pressure, was then exploited for experiments involving cavity cooling [3], and coherent amplification in the form of a phonon laser [4].
CRIS-Team Scopus Importer:2021-10-29

Kerr-Nonlinearity-Induced Mode-Splitting in Optical Microresonators - Ghalanos, George N.; Silver, Jonathan M.; Del Bino, Leonardo; Moroney, Niall; Zhang, Shuangyou; Woodley, Michael T. M.; Svela, Andreas O.; Del'Haye, Pascal (Physical Review Letters, 2020)
The Kerr effect in optical microresonators plays an important role for integrated photonic devices and enables third harmonic generation, four-wave mixing, and the generation of microresonator-based frequency combs. Here we experimentally demonstrate that the Kerr nonlinearity can split ultra-high-Q microresonator resonances for two continuous-wave lasers. The resonance splitting is induced by self- and cross-phase modulation and counterintuitively enables two lasers at different wavelengths to be simultaneously resonant in the same microresonator mode. We develop a pump-probe spectroscopy scheme that allows us to measure power dependent resonance splittings of up to 35 cavity linewidths (corresponding to 52 MHz) at 10 mW of pump power. The required power to split the resonance by one cavity linewidth is only 286 mu W. In addition, we demonstrate threefold resonance splitting when taking into account four-wave mixing and two counterpropagating probe lasers. These Kerr splittings are of interest for applications that require two resonances at optically controlled offsets, e.g., for optomechanical coupling to phonon modes, optical memories, and precisely adjustable spectral filters.
CRIS-Team WoS Importer:2020-06-19

Light Distribution Patterns in Microresonator Chain PICs with Kerr-Nonlinearity - Ghosh, Alekhya; Pal, Arghadeep; Hill, Lewis; Campbell, Graeme N.; Bi, Toby; Zhang, Yaojing; Alabbadi, Abdullah; Zhang, Shuangyou; Del'Haye, Pascal (British and Irish Conference on Optics and Photonics, BICOP 2024 in Proceedings British and Irish Conference on Optics and Photonics 2024, 2024)
We demonstrate control of optical power patterns in one-dimensional photonic lattices of coupled resonator optical waveguides (CROWS) induced by the Kerr effect. This can advance photonic integrated circuits, especially for light steering and optical computing.
CRIS-Team Scopus Importer:2025-04-01

Light Dynamics in Twin Microresonators with Tunable Coupling - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Shuangyou; Hill, Lewis; Yan, Haochen; Zhang, Hao; Bi, Toby; Alabbadi, Abdullah; Del'Haye, Pascal (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
Low threshold power in Kerr-microresonators have made them attractive platforms for observing nonlinear interactions of light. Previous works on single microresonators reported light distribution between different modes, including slow-time evolutions [1,2] as well as the fast-time dynamics of optical fields [3], along with dispersion engineering [4]. Coupled resonator systems have gathered significant attention in recent years for unveiling a wide range of novel physical phenomena such as spontaneous symmetry breaking [5,6], and investigations of soliton dynamics [7].
CRIS-Team Scopus Importer:2025-09-26

Linear and Nonlinear Interactions in Hybrid Microresonators with Controllable Coupling - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Hao; Ghalanos, George; Bi, Toby; Zhang, Shuangyou; Hill, Lewis; Del'Haye, Pascal (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We investigate linear and nonlinear dynamics of light in coupled resonators. In our experiments, we can adjust the coupling gap between two resonators in real-time to study symmetry breaking of hybridized counterpropagating modes.
CRIS-Team Scopus Importer:2024-10-04

Long-Range “Talking” of Vector Solitons and their Synchronization in Fabry-Pérot Resonators - Hill, Lewis; Hirmer, Eva Maria; Campbell, Graeme; Bi, Toby; Ghosh, Alekhya; Oppo, Gian Luca; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
A suitable Fabry-Pérot (FP) cavity, Fig. 1(a), filled with a Kerr medium with anomalous dispersion can support temporal cavity solitons (TCS) [1]. Kerr FP cavities have also been shown to exhibit a spontaneous symmetry breaking (SSB) [2] between the powers of orthogonally polarized light components [3]. Just as these phenomena have been combined in Kerr ring resonators [4,5], we investigate the SSB of TCS in Kerr linear resonators. Figure 1(b) shows this SSB of TCS, where, in the vector soliton pair, one notes that one polarization is dominant over the other, thus realizing a linear cavity source of symmetry broken vectorial Kerr frequency combs, Fig. 1(c). We discuss here a number of further, fascinating and useful, results not possible in the previous Kerr ring studies.
CRIS-Team Scopus Importer:2024-12-16

Low-Temperature Sputtered Ultralow-Loss Silicon Nitride for Hybrid Photonic Integration - Zhang, Shuangyou; Bi, Toby; Harder, Irina; Ohletz, Olga; Gannott, Florentina; Gumann, Alexander; Butzen, Eduard; Zhang, Yaojing; Del'Haye, Pascal (Laser & Photonics Reviews, 2024)
Silicon-nitride-on-insulator (Si3N4) photonic circuits have seen tremendous advances in many applications, such as on-chip frequency combs, Lidar, telecommunications, and spectroscopy. So far, the best film quality has been achieved with low pressure chemical vapor deposition (LPCVD) and high-temperature annealing (1200°C). However, high processing temperatures pose challenges to the cointegration of Si3N4 with pre-processed silicon electronic and photonic devices, lithium niobate on insulator (LNOI), and Ge-on-Si photodiodes. This limits LPCVD as a front-end-of-line process. Here, ultralow-loss Si3N4 photonics based on room-temperature reactive sputtering is demonstrated. Propagation losses as low as 5.4 dB m−1 after 400°C annealing and 3.5 dB m−1 after 800°C annealing are achieved, enabling ring resonators with highest optical quality factors of > 10 million and an average quality factor of 7.5 million. To the best of the knowledge, these are the lowest propagation losses achieved with low temperature Si3N4. This ultralow loss enables the generation of microresonator soliton frequency combs with threshold powers of 1.1 mW. The introduced sputtering process offers full complementary metal oxide semiconductor (CMOS) compatibility with front-end silicon electronics and photonics. This could enable hybrid 3D integration of low loss waveguides with integrated lasers and lithium niobate on insulator.
CRIS-Team Scopus Importer:2024-04-12
Keywords: hybrid photonic integration; low-temperature sputtering; silicon nitride; soliton frequency comb

Low-Temperature Sputtered Ultralow-Loss Silicon Nitride for Integrated Photonics - Zhang, Shuangyou; Bi, Toby; Harder, Irina; Lohse, Olga; Gannott, Florentina; Gumann, Alexander; Butzen, Eduard; Zhang, Yaojing; Del'Haye, Pascal (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We demonstrate ultralow-loss, high-thickness silicon nitride waveguides and microresonators based on room-temperature sputtering. We reach propagation losses of 3.5 dB/m after 800 °C annealing, enabling ring resonators with optical quality factors >10 million.
CRIS-Team Scopus Importer:2024-10-04

Microresonator logic gates with counterpropagating light - Moroney, Niall; Del Bino, Leonardo; Woodley, Michael T.M.; Silver, Jonathan; Ghalanos, George N.; Svela, Andreas; Zhang, Shuangyou; Del'Haye, Pascal (Optics InfoBase Conference Papers, 2020)
We use kerr-interaction between counter-propagating light waves in a whispering gallery mode resonator to demonstrate a universal, all-optical, logic gate. This provides a novel path for on-chip routing of light.
CRIS-Team Scopus Importer:2024-12-16

Microresonator Soliton Frequency Combs Enabled by Quintic Dispersion - Bi, Toby; Zhang, Shuangyou; Hill, Lewis; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Recent advances in fabrication and precision measurement techniques for dispersion engineering have enabled soliton frequency combs to operate in the near-zero GVD regime in microresonators [1,2]. These particular frequency combs are phase-matched through higher-order dispersion, usually via third-order dispersion. With low variation in the resonator mode spacing and the emission of dispersive waves, near-zero GVD frequency combs are able to cover a broad frequency range. In this work, we present near-zero GVD solitons experimentally generated in a microresonator using a continuous-wave (CW) source where the dominant higher-order dispersion term is fifth-order (5th-OD). We also numerically verify the existence of 5th-OD enabled solitons. This constitutes the first observation of near-zero GVD solitons pumped by a CW laser and the first observation of generated solitons dominated by fifth-order dispersion (FiOD) [3].
CRIS-Team Scopus Importer:2024-12-16

Mode Splitting in Silicon Nitride Ring Resonators via Partial Sidewall Modulation - Kheyri, Masoud; Zhang, Shuangyou; Bi, Toby; Pal, Arghadeep; Zhang, Hao; Zhang, Yaojing; Alabbadi, Abdullah; Butzen, Eduard; Gannott, Florentina; Gumann, Alexander; Harder, Irina; Ohletz, Olga; et al. (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We investigate mode splitting in silicon nitride microresonators that is induced by modulating the resonator sidewall with different amplitudes and modulation lengths. This offers important insights for microresonator dispersion engineering for photonic integrated circuits.
CRIS-Team Scopus Importer:2024-10-04

More Than 34 dB Backscattering Suppression in Microresonators - Svela, Andreas O.; Silver, Jonathan M.; Del Bino, Leonardo; Zhang, Shuangyou; Woodley, Michael T.M.; Vanner, Michael R.; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Optical modes in whispering-gallery-mode (WGM) resonators generally come in pairs of degenerate modes with opposite propagation directions: a clockwise and a counter-clockwise mode. However, sub-wavelength-size imperfections on the surface and in the bulk material of the resonators, usually cause some amount of Rayleigh scattering between the modes [1]. For sufficiently high levels of backscattering, the coupling between the modes can be observed as a resolvable splitting in the frequency domain [2]. Coupling of the modes is unfavourable for some WGM resonator applications, for example gyroscopes [3] , dual frequency combs [4] , and applications relying on symmetry breaking of counter-propagating light [5] , [6].
CRIS-Team Scopus Importer:2021-10-29

Multi-stage spontaneous symmetry breaking of light in Kerr ring resonators - Hill, Lewis; Oppo, Gian Luca; Del'Haye, Pascal (Communications Physics, 2023)
Symmetry breaking of light states is of interest for the understanding of nonlinear optics, photonic circuits, telecom applications and optical pulse generation. Here we demonstrate multi-stage symmetry breaking of the resonances of ring resonators with Kerr nonlinearity. This multi-stage symmetry breaking naturally occurs in a resonator with bidirectionally propagating light with orthogonal polarization components. The derived model used to theoretically describe the system shows that the four circulating field components can display full symmetry, full asymmetry, and multiple versions of partial symmetry, and are later shown to result in complex oscillatory dynamics - such as four-field self-switching, and unusual pulsing with extended delays between subsequent peaks. To highlight a few examples, our work has application in the development of photonic devices like isolators and circulators, logic gates, and random numbers generators, and could also be used for optical-sensors, e.g. by further enhancing the Sagnac effect.
CRIS-Team Scopus Importer:2024-12-16

Nonlinear enhanced microresonator gyroscope - Silver, Jonathan M.; Del Bino, Leonardo; Woodley, Michael T. M.; Ghalanos, George N.; Svela, Andreas O.; Moroney, Niall; Zhang, Shuangyou; Grattan, Kenneth T.; Del'Haye, Pascal (Optica, 2021)
Optical gyroscopes based on the Sagnac effect have been the mainstay of inertial navigation in aerospace and shipping for decades. These gyroscopes are typically realized either as ring-laser gyroscopes (RLGs) or fiber-optic gyroscopes (FOGs). With the recent rapid progress in the field of ultrahigh-quality optical whispering-gallery mode and ring microresonators, attention has been focused on the development of microresonator-based Sagnac gyroscopes as a more compact alternative to RLGs and FOGs. One avenue that has been explored is the use of exceptional points in non-Hermitian systems to enhance the responsivity to rotation. We use a similar phenomenon, namely, the critical point of a spontaneous symmetry-breaking transition between counterpropagating light, to demonstrate a microresonator gyroscope with a responsivity enhanced by a factor of around 10(4). We present a proof-of-principle rotation measurement as well as a characterization of the system's dynamical response, which shows the universal critical behaviors of responsivity enhancement and critical slowing down, both of which are beneficial in an optical gyroscope. We believe that this concept could be used to realize simple and cheap chip-based gyroscopes with sensitivities approaching those of today's RLGs and FOGs. (C) 2021 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2021-10-08

Nonlinear Optics with Coupled Twin-Microresonators - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Shuangyou; Hill, Lewis; Yan, Haochen; Zhang, Hao; Bi, Toby; Alabbadi, Abdullah; Del'Haye, Pascal (British and Irish Conference on Optics and Photonics, BICOP 2024 in Proceedings British and Irish Conference on Optics and Photonics 2024, 2024)
Linear and nonlinear light interactions in coupled microresonators are investigated. In our experiments, we can tune the coupling gap between two resonators to investigate symmetry breaking of hybridized counterpropagating modes.
CRIS-Team Scopus Importer:2025-04-01

Nonlinear phase switching in microresonators for all-optical computing PICs - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Shuangyou; Hill, Lewis; Bi, Toby; Del'Haye, Pascal (British and Irish Conference on Optics and Photonics, BICOP 2024 in Proceedings British and Irish Conference on Optics and Photonics 2024, 2024)
An optical switch and proposed designs of photonic logic gates exploiting Kerr-effect-mediated phase control of light waves are presented. Our results can be used for integrated all-optical computing and telecom applications.
CRIS-Team Scopus Importer:2025-04-01

On-Chip Inverse Designed Fabry-Pérot Resonators - Bi, Toby; Zhang, Shuangyou; Ghosh, Alekhya; Lohse, Olga; Harder, Irina; Yang, Ki Youl; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Silicon nitride (Si3N4) is emerging as the forerunner for integrated photonic microresonator devices due to its wide transparency window from 0.47 to 6.7 µm, relatively large third-order nonlinearity, and a complementary metal-oxide semiconductor compatible fabrication process that ensures low propagation losses. The advances in the Si3N4 platform have led to tremendous growth in the fields of optical telecommunications, spectroscopy, and astronomical instrument calibration. Traditional on-chip microresonators are waveguide ring resonators that are evanescently coupled via a bus waveguide. Recently, a paradigm shift towards on-chip Si3N4 microcavities based on the Fabry-Pérot resonators has emerged [1,2]. These cavities can be formed when a central waveguide has two Bragg-like reflectors on either side. One advantage of using a linear cavity is gaining extra degrees of freedom for dispersion engineering through sub-micron structuring of the reflectors. In this work, we use broadband inverse-designed reflectors [3,4] to realize high-Q on-chip linear Si3N4 microresonators.
CRIS-Team Scopus Importer:2024-12-16

Optical Memory Based on Conterpropagating Light in Microresonators - Bino, Leonardo Del; Moroney, Niall; Del'Haye, Pascal (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
A consequence of the Kerr effect in ring microresonators is that light can not always circulate simultaneously in both directions. Instead, under the appropriate conditions of input power and detuning, light can couple into the resonator only in one direction while the other continues on the coupling waveguide [1] - [3]. The two resulting light states, clockwise (CW) and counterclockwise (CCW), can be interpreted as the digital states 1 and 0 as shown in Fig. 1 (c). Microresonators have been theorized to be a suitable solution for on-chip logical processing and switching [4]. Here we present an all-optical bistable device based on the difference of the Kerr effect for co-propagating and counterpropagating light. The device does not require any electrical power, and relies only on a single laser input for its operation. The optical state is set by the dominant input power direction. The system exhibits hysteresis ( Fig. 1 (d) ) hence the optical state is maintained until an significant input in the opposite direction is received. The hysteresis provides resilience to fluctuations in the inputs up to half of the total input power.
CRIS-Team Scopus Importer:2021-10-29

Phase Symmetry Breaking for All-Optical Computing with Microresonators - Pal, Arghadeep; Ghosh, Alekhya; Zhang, Shuangyou; Hill, Lewis; Bi, Toby; Del'Haye, Pascal (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
Current fiber optic technology suffers from scalability limitations, preventing its use in real-time data processing in optical communications systems and photonic networks. Major challenges are optical to electronic (and vice-versa) signal conversions, which introduce additional complexity. Upcoming all-optical circuits [1] can resolve this issue by reducing the latency related to such conversions, however, they require comparably high optical power to operate. Kerr-microresonators provide an interesting platform for developing all-optical circuits using nonlinear effects at much lower threshold power.
CRIS-Team Scopus Importer:2025-09-26

Phase Symmetry Breaking of Counterpropagating Light in Microresonators for Switches and Logic Gates - Ghosh, Alekhya; Pal, Arghadeep; Zhang, Shuangyou; Hill, Lewis; Bi, Toby; Del'Haye, Pascal (Laser & Photonics Reviews, 2025)
The rapidly growing field of integrated photonics is enabling a large number of novel devices for optical data processing, neuromorphic computing and circuits for quantum photonics. While many photonic devices are based on linear optics, nonlinear responses at low threshold power are of high interest for optical switching and computing. In the case of counterpropagating light, nonlinear interactions can be utilized for chip-based isolators and logic gates. In this work, a symmetry breaking of the phases of counterpropagating light waves is found in high-Q ring resonators. This abrupt change in the phases can be used for optical switches and logic gates. In addition to these experimental results, theoretical models are provided that describe the phase symmetry breaking of counterpropagating light in ring resonators.
CRIS-Team Scopus Importer:2025-09-12
Keywords: microresonators; optical switching; phase asymmetry; photonic computing; spontaneous symmetry breaking

Proposal for a hybrid clock system consisting of passive and active optical clocks and a fully stabilized microcomb - Yu, Deshui; Vollmer, Frank; Del'Haye, Pascal; Zhang, Shougang (Optics Express, 2023)
Optical atomic clocks produce highly stable frequency standards and frequency combs bridge clock frequencies with hundreds of terahertz difference. In this paper, we propose a hybrid clock scheme, where a light source pumps an active optical clock through a microresonator-based nonlinear third harmonic process, serves as a passive optical clock via indirectly locking its frequency to an atomic transition, and drives a chip-scale microcomb whose mode spacing is stabilized using the active optical clock. The operation of the whole hybrid system is investigated through simulation analysis. The numerical results show: (i) The short-term frequency stability of the passive optical clock follows an Allan deviation of σy(τ) = 9.3 × 10−14τ−1/2 with the averaging time τ, limited by the population fluctuations of interrogated atoms. (ii) The frequency stability of the active optical clock reaches σy(τ) = 6.2 × 10−15τ−1/2, which is close to the quantum noise limit. (iii) The mode spacing of the stabilized microcomb has a shot-noise-limited Allan deviation of σy(τ) = 1.9 × 10−11τ−1/2. Our hybrid scheme may be realized using recently developed technologies in (micro)photonics and atomic physics, paving the way towards on-chip optical frequency comparison, synthesis, and synchronization.
CRIS-Team Scopus Importer:2023-02-24

Pure Quintic Dispersion Microresonator Frequency Combs - Bi, Toby; Zhang, Shuangyou; Hill, Lewis; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
Pure fifth-order chromatic dispersion-based frequency combs are theoretically and numerically investigated. We find that multiple bright, dark, and multi-peak soliton solutions exist simultaneously.
CRIS-Team Scopus Importer:2023-11-24

Quintic Dispersion Soliton Frequency Combs in a Microresonator - Zhang, Shuangyou; Bi, Toby; Del'Haye, Pascal (Laser & Photonics Reviews, 2023)
Chip-scale optical frequency combs have attracted significant research interest and can be used in applications ranging from precision spectroscopy to telecom channel generators and lidar systems. In the time domain, microresonator based frequency combs correspond to self-stabilized soliton pulses. In two distinct regimes, microresonators are shown to emit either bright solitons in the anomalous dispersion regime or dark solitons (a short time of darkness in a bright background signal) in the normal dispersion regime. Here, the dynamics of continuous-wave-laser-driven soliton generation is investigated in the zero-group-velocity-dispersion regime as well as the generation of solitons that are spectrally crossing different dispersion regimes. In the measurements, zero-dispersion solitons with multipeak structures (soliton molecules) are observed with distinct and predictable spectral envelopes that are a result of fifth-order dispersion of the resonators. Numerical simulations and the analysis of bifurcation structures agree well with the observed soliton states. This is the first observation of soliton generation that is governed by fifth-order dispersion, which can have applications in ultrafast optics, telecom systems, and optical spectroscopy.
CRIS-Team Scopus Importer:2023-05-26
Keywords: frequency comb; high-order dispersion; quintic dispersion; soliton

Raman Frequency Combs in Integrated Silicon Nitride Microresonators - Ghosh, Alekhya; Pal, Arghadeep; Zhang, Shuangyou; Bi, Toby; Kheyri, Masoud; Yan, Haochen; Zhang, Yaojing; Del'Haye, Pascal (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
Raman effects [1,2] have been extensively studied in integrated photonics for the generation of new optical frequencies at low powers. Kerr microresonators are efficient tools for observing various optical nonlinearities [3,4] due to their small mode volumes and high-quality (Q) factors. In microresonators, the interplay of Raman and Kerr effects leads to the formation of Raman-Kerr optical frequency combs and has been reported for different materials like silica, lithium niobate and silicon carbide [5-7]. The Raman gain is very low in silicon nitride (Si3N4) microresonators and thus Raman effects have not been directly observed. On the other hand, the Raman effect in silica (SiO2) resonators is well-known [3]. Here, we engineer the microresonator's geometry to optimize the optical field overlap between the core (Si3N4) and cladding (SiO2) regions. The cladding material initiates the Raman effect, thereby producing a strong Raman signal. The high Kerr-coefficient of the core material facilitates the generation of additional frequency sidebands due to nondegenerate four-wave mixing between the pump and the Stokes waves. Our approach enables comb generation by triggering the different nonlinearities in both the core and the cladding of the microresonator.
CRIS-Team Scopus Importer:2025-09-26

Room temperature sputtered silicon nitride microcombs and real-Time Hz-level tunable laser spectroscopy - Bi, Toby; Zhang, Shuangyou; Harder, Irina; Ohletz, Olga; Gannott, Florentina; Gumann, Alexander; Butzen, Eduard; Zhang, Yaojing; Del'Haye, Pascal (Proceedings of SPIE - The International Society for Optical Engineering, 2025)
Reactively sputtered silicon nitride thin films offer the combination of ultralow optical losses, film thickness above >700nm in a single deposition step, and low processing temperature. Employing this process, we demonstrate microresonators exhibiting Q-factors of 1 million without thermal annealing and 10 million with 800°C thermal annealing in the L-band. Since the waveguides of the ring resonators exhibit anomalous dispersion soliton microcombs can be generated. We will also present a tunable laser spectroscopy scheme where a frequency modulated tunable diode laser is referenced to a fiber cavity. The fiber cavity free-spectral range is determined, in real time, to a sub 10-Hz level over a spectral range of 11 THz at a scanning speed of 1 THz/s. The scheme is applied onto dispersion measurements of integrated microresonators.
CRIS-Team Scopus Importer:2025-09-05
Keywords: microresonators; Nanophotonics; silicon nitride; spectroscopy

Room-temperature Sputtered Ultralow-loss Silicon Nitride - Zhang, Shuangyou; Bi, Toby; Harder, Irina; Lohse, Olga; Gannott, Florentina; Gumann, Alexander; Zhang, Yaojing; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Silicon nitride films with the best optical quality can be realized with low pressure chemical vapor deposition (LPCVD) [1]. However, high mechanical stress within the LPCVD silicon nitride films leads to formation of cracks and prevents thick films (> 400 nm) with high optical quality. A number of clever processes have been developed in order to prevent cracks, such as patterning of crack barriers, multi-step deposition and a Damascene process that deposits silicon nitride into trenches. In addition, to reduce material losses and achieve ultralow propagation losses ( 1 dB/m), long-time high temperature annealing (1200 °C for 3 hours) is needed, which can cause dopant diffusion and damage of prefabricated temperature-sensitive devices. Hence, LPCVD Si3N4 is very challenging for applications in back-end-of-line processes and foundry compatible processes. In recent years, low-temperature deposited Si3N4 thin films have attracted increasing interest for 3D hybrid integration of Si3N4 with other materials. Here we report the fabrication of ultralow-loss Si3N4 photonics film by reactive sputtering at room temperature [2]. Directly after room-temperature sputtering, the Si3N4 film loss is 32 dB/m without thermal annealing and the intrinsic optical quality factor (Q) of the fabricated microresonators is 1.1 million in the L-band. This propagation loss is already lower than that of annealing-free LPCVD Si3N4 film deposited at 780 °C [3].
CRIS-Team Scopus Importer:2023-12-15

Selective Laser-induced Etching for novel 3D microphotonic devices - Beckmann, Lara; Bi, Toby; Thoms, Julian M.; Wenk, Max; Zhang, Shuangyou; Kratz, Martin; Del'Haye, Pascal (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2024)
In this work, we evaluate the advantages and limitations of the Selective Laser-induced Etching (SLE) process for the fabrication of novel three-dimensional microresonator structures. Microresonators are resonant optical structures with the ability to store light of a specific wavelength. They are used as non-linear optical components, in sensors or even in integrated photonic devices. These structures are characterized by the optical quality factor Q as a measure of the optical storage capabilities. Q is significantly influenced by a high-quality optical surface with low surface roughness. In addition to surface quality and small dimensions, from tens of microns to millimeters, high optical nonlinearity is a key requirement in these fields. The fabrication of 3D fused silica parts fulfilling these requirements is an ongoing challenge in the field of microfabrication in quantum technology. The SLE process is used to fabricate three-dimensional parts of transparent materials such as fused silica with a high degree of geometric freedom in a two-step process. In the first step, a model of the part is written into the material using ultrashort pulse (USP) laser radiation. In the second step, the laser-written shape is wet-chemically etched in aqueous KOH to expose the part. The fabrication of 2D disk microresonators with high Q-factors is evaluated by studying the surface roughness of the SLE process followed by polishing. The polished samples are characterized and Q-factors >107 are achieved. In addition, the extent to which dimensions and geometry differ between design and real SLE components is analyzed. The SLE process will thus be investigated as a possible process for the future fabrication of three-dimensional microresonators.
CRIS-Team Scopus Importer:2024-05-03
Keywords: 3D micromachining; fused silica; in-volume structuring; laser micromachining; microresonators; selective laser-induced etching; SLE; ultrashort pulsed

Self-Switching Kerr Oscillations of Counterpropagating Light in Microresonators - Woodley, Michael T.M.; Hill, Lewis; Del Bino, Leonardo; Oppo, Gian Luca; Del'Haye, Pascal (Physical Review Letters, 2021)
We report the experimental and numerical observation of oscillatory antiphase switching between counterpropagating light beams in Kerr ring microresonators, where dominance between the intensities of the two beams is periodically or chaotically exchanged. Self-switching occurs in balanced regimes of operation and is well captured by a simple coupled dynamical system featuring only the self- and cross-phase Kerr nonlinearities. Switching phenomena are due to temporal instabilities of symmetry-broken states combined with attractor merging, which restores the broken symmetry on average. Self-switching of counterpropagating light is robust for realizing controllable, all-optical generation of waveforms, signal encoding, and chaotic cryptography.
CRIS-Team Scopus Importer:2021-02-12

Soliton Frequency Combs via Cascaded Brillouin Scattering - Zhang, Hao; Zhang, Shuangyou; Bi, Toby; Ghalanos, George; Zhang, Yaojing; Yan, Haochen; Pal, Arghadeep; He, Jijun; Pan, Shilong; Del'Haye, Pascal (CLEO: Science and Innovations, CLEO: S and I 2024 in Proceedings CLEO 2024, Part of Conference on Lasers and Electro-Optics, 2024)
We present Kerr soliton generation via a forward propagating second order Brillouin scattering process in a microresonator. The solitons repetition rates are independent from the Brillouin gain frequency shift ( 10 GHz in fused silica).
CRIS-Team Scopus Importer:2024-10-04

Spectral extension and synchronization of microcombs in a single microresonator - Zhang, Shuangyou; Silver, Jonathan M.; Bi, Toby; Del'Haye, Pascal (Nature Communications, 2020)
Broadband optical frequency combs are extremely versatile tools for precision spectroscopy, ultrafast ranging, as channel generators for telecom networks, and for many other metrology applications. Here, we demonstrate that the optical spectrum of a soliton microcomb generated in a microresonator can be extended by bichromatic pumping: one laser with a wavelength in the anomalous dispersion regime of the microresonator generates a bright soliton microcomb while another laser in the normal dispersion regime both compensates the thermal effect of the microresonator and generates a repetition-rate-synchronized second frequency comb. Numerical simulations agree well with experimental results and reveal that a bright optical pulse from the second pump is passively formed in the normal dispersion regime and trapped by the primary soliton. In addition, we demonstrate that a dispersive wave can be generated and influenced by cross-phase-modulation-mediated repetition-rate synchronization of the two combs. The demonstrated technique provides an alternative way to generate broadband microcombs and enables the selective enhancement of optical power in specific parts of a comb spectrum.
CRIS-Team Scopus Importer:2020-12-25

Spectral extension of microcombs with two seed lasers - Zhang, Shuangyou; Silver, Jonathan M.; Bi, Toby; Del'Haye, Pascal (Optics InfoBase Conference Papers, 2021)
We demonstrate the spectral extension of microcombs by bichromatic pumping of a single microresonator. One of the seed lasers generates a soliton that synchronizes with the repetition rate of the second frequency comb via cross-phase modulation.
CRIS-Team Scopus Importer:2021-12-03

Splitting microresonator modes with the kerr-nonlinearity - Ghalanos, George N.; Silver, Jonathan M.; Bino, Leonardo Del; Moroney, Niall; Zhang, Shuangyou; Woodley, Michael T.M.; Svela, Andreas; Del'Haye, Pascal (Optics InfoBase Conference Papers, 2020)
We observe two-fold and three-fold splitting of optical modes in ultra-high-Q microresonators induced by the Kerr effect. This can be used for applications that require multiple resonances with precisely controlled offset.
CRIS-Team Scopus Importer:2024-12-16

Spontaneous Symmetry Breaking of Cavity Solitons in Coupled Resonators - Ghosh, Alekhya; Pal, Arghadeep; Hill, Lewis; Yan, Haochen; Oppo, Gian Luca; Del'Haye, Pascal (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
Coupled resonator systems have recently gained extensive interest for their ability to control the nonlinear interactions of light. The interplay of linear inter-resonator light scattering and Kerr-nonlinearities make these platforms suitable for tuning dispersion, and controlling soliton dynamics [1]. Spontaneous symmetry breaking (SSB) in chirality [2] and polarization [3] of light fields are typically observed in single Kerr-resonators. Coupled resonators can show higher dimensional SSBs [4-6]. Here, we examine SSB between counterpropagating homogeneous light fields and soliton states in coupled twin resonator systems.
CRIS-Team Scopus Importer:2025-09-26

Spontaneous symmetry breaking of Kerr solitons in Fabry Perot Resonators - Hill, Lewis; Hirmer, Eva Maria; Campbell, Graeme; Ghosh, Alekhya; Bi, Toby; Oppo, Gian Luca; Del'Haye, Pascal (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
Symmetry breaking of vector temporal cavity solitons in Fabry-Perot resonators is presented. This work can improve the generation of frequency combs through its control of the number of cavity solitons in a round trip.
CRIS-Team Scopus Importer:2023-11-24